2019
DOI: 10.1007/s00213-019-05232-0
|View full text |Cite
|
Sign up to set email alerts
|

A potential role for the gut microbiome in substance use disorders

Abstract: Pathological substance use disorders represent a major public health crisis with limited effective treatment options. While much work has been done to understand the neuronal signaling networks and intracellular signaling cascades associated with prolonged drug use, these studies have yielded few successful treatment options for substance use disorders. In recent years, there has been a growing interest to explore interactions between the peripheral immune system, the gut microbiome and the CNS. In this review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
93
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(98 citation statements)
references
References 182 publications
(333 reference statements)
2
93
0
Order By: Relevance
“…Although we have demonstrated that berberine facilitates the extinction of drug-associated behavior by enhancing consolidation of extinction memory, further studies are required to explore potential direct targets of berberine. A number of CNS diseases have been linked to abnormalities of gastrointestinal tract and recent studies suggest that gut microbiota plays a key role in the development of drug addiction (Kiraly et al, 2016;Ning et al, 2017;Meckel and Kiraly, 2019). Moreover, remarkable effects of berberine on gut microbiota and regulation of related disease pathophysiology have been recently reported (Cui et al, 2018;Feng et al, 2019;Yue et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Although we have demonstrated that berberine facilitates the extinction of drug-associated behavior by enhancing consolidation of extinction memory, further studies are required to explore potential direct targets of berberine. A number of CNS diseases have been linked to abnormalities of gastrointestinal tract and recent studies suggest that gut microbiota plays a key role in the development of drug addiction (Kiraly et al, 2016;Ning et al, 2017;Meckel and Kiraly, 2019). Moreover, remarkable effects of berberine on gut microbiota and regulation of related disease pathophysiology have been recently reported (Cui et al, 2018;Feng et al, 2019;Yue et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in morphine-addicted rats indicate that next to changes in AA and biogenic amine-metabolism, disruption of energy metabolism is of especially high relevance in morphine addiction, as alterations in urine TCA-cycle metabolites were observed in rats [62]. In recent years, growing research interest emphasized on the interactions between the central nervous system and the gut microbiome have revealed a potential contribution of gut dysbiosis in the pathogenesis of addictive disorders [79]. Wang et al [78] explored the gut metabolomic profile of morphine-addicted mice, to identify functional changes in the gut microbiome, as gut metabolites represent an important link between the gastrointestinal microbiome and the biological functions of the host.…”
Section: Metabolomics In Addictive Disordersmentioning
confidence: 99%
“…Animal models are not only required for the direct study of brain metabolites but also in the study of the gut microbiome. While the human microbiome is the product of complex environmental interactions and highly diverse [107], germ-free animals that are raised in sterile environments enable the investigation of the effects of the gut microbiome on behavior [79,108]. Animals lacking any internal or external microbiome can be colonized with microbial communities from donor animals or humans, to elucidate the contribution of a defined microbiome to a phenotype of interest [108].…”
Section: Strengths and Limitations Of Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing emphasis on the potential role for the gut microbiome in substance use disorders and this is reviewed by Meckel and Kiraly (Meckel and Kiraly 2019). This is supported by a research paper focusing on the impact of alcohol-induced changes on the gut microbiome and metabolome in rhesus macaques (Zhang et al 2019).…”
mentioning
confidence: 99%